2020
DOI: 10.1001/jamaoncol.2020.4643
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific and Targeted Therapy Based on Molecular Profiling by Next-Generation Sequencing for Cancer of Unknown Primary Site

Abstract: IMPORTANCEAlthough profiling of gene expression and gene alterations by next-generation sequencing (NGS) to predict the primary tumor site and guide molecularly targeted therapy might be expected to improve clinical outcomes for cancer of unknown primary site (CUP), to our knowledge, no clinical trial has previously evaluated this approach.OBJECTIVE To assess the clinical use of site-specific treatment, including molecularly targeted therapy based on NGS results, for patients with CUP.DESIGN, SETTING, AND PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 36 publications
0
77
0
2
Order By: Relevance
“…Furthermore, several patients with ERBB2 amplification, BRAFV600E mutation, KIF5B-ALK fusion, NCOA4-RET fusion, FGFR2/3 fusion, and IRF2BP-NTRK1 fusion showed a response to matched specific kinase inhibitors [12]. In a trial conducted by Hayashi et al, precision therapy, based on NGS (molecular targeted therapy), was performed for CUP [6]. EGFR mutations (E709G, L861Q, R776C, and G719C) were detected in five of the ninety-seven patients in their trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several patients with ERBB2 amplification, BRAFV600E mutation, KIF5B-ALK fusion, NCOA4-RET fusion, FGFR2/3 fusion, and IRF2BP-NTRK1 fusion showed a response to matched specific kinase inhibitors [12]. In a trial conducted by Hayashi et al, precision therapy, based on NGS (molecular targeted therapy), was performed for CUP [6]. EGFR mutations (E709G, L861Q, R776C, and G719C) were detected in five of the ninety-seven patients in their trial.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment strategy for CUP is a site-specific therapy, based on histopathological features, determined through immunohistochemistry [3][4][5], or gene expression and gene alterations, detected by next-generation sequencing (NGS). Hayashi et al reported that genetically matched molecular targeted therapy, based on site-specific treatment evaluated by NGS, could be used to treat patients with CUP, a type of cancer, whose prognosis is unfavorable [6]. In the CUPISCO trial, anaplastic lymphoma kinase (ALK) rearrangement was detected in 0.7% of the cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…These findings will contribute to the identification of the appropriate timing and clinical stage at which clinical sequencing should be performed according to tumor type. Considering that some patients with refractory solid tumor (such as rare tumors and pancreato-biliary cancer) experience impressive responses to targeted therapy following genetic tests [11,12,28], we recommend that clinical sequencing for those patients be performed at an earlier stage (i.e., at the time of tumor diagnosis or prior to standard chemotherapy).…”
Section: Plos Onementioning
confidence: 99%
“…There have been significant advances in precision oncology, with an increasing adoption of sequencing tests that identify targetable mutations in cancer driver genes. Aiming to complement these efforts by considering genome-wide tumor alterations at additional ''-omics'' layers, recent studies have begun to explore the utilization of transcriptomics data to guide cancer patients' treatment (Beaubier et al, 2019;Hayashi et al, 2020;Rodon et al, 2019;Tanioka et al, 2018;Vaske et al, 2019;Wong et al, 2020). These studies have reported encouraging results, testifying to the potential of such approaches to comple-ment mutation panels and increase the likelihood that patients will benefit from genomics-guided precision treatments.…”
Section: Introductionmentioning
confidence: 99%